(untitled) (Research, Society and Development, 2021)
The objective is to alert about the possible role of viral infections caused by the mouse mammary tumor virus (MMTV) in the development and progression of breast cancer (BC), emphasizing the prevalence of the virus finding in this pathology, and its determinant action in the carcinogenic clinical outcome. In this work, a bibliographical survey was carried out, searching for scientific productions published in PubMed, LILACS and SciELO journals. From this survey, a systematic review was carried out, using scientific articles from the last 5 years, in Portuguese, Spanish and English versions. Generally, studies carried out with Polymerase Chain Reaction (PCR) and hybridization techniques were taken into consideration. Thus, a prevalence of mammary carcinogenesis induced by the mouse mammary tumor virus (mean 31.6%) was observed when compared to the occasion when the virus finding was positive but not inducing such pathology. In addition, when the virus was positive, inducing carcinogenesis, the inhibition of lymph node metastasis was evidenced. Thus, the mouse mammary tumor virus is consolidated as a risk factor for the development of breast cancer. Moreover, the finding of the virus in breast cancer was associated with a better prognosis, by inhibiting blood/lymphatic dissemination of tumor cells. Therefore, from the possibility that tumor cells may display viral antigens, a potential antigenic target is established, with the promise of developing preventive treatments for breast cancer.